Commentary on Solms: On the mechanisms of repression and defence. Issue 1 (2nd July 2020) - Boag, Simon
ABSTRACT: Mark Solms provides a sophisticated extension and clarification of Freud's Project in light of current neuropsychoanalytic thinking and Friston's free-energy principle. This commentary focuses upon Solms' view of repression and defence in his updated Project, whereby Solms extends his recent work on the topic. After noting similarities and differences between Freud's and Solms' views on repression and defense, the commentary addresses the proposed mechanism of repression in Solms' revised Project. An analysis of Solms' account indicates there is not as yet a coherent mechanism of repression in his revised Project, although some type of plausible neural mechanism may nevertheless still be theoretically possible. Consequently, although there is likely merit in Solms' position on repression and defence, there are still outstanding questions that need addressing before this merit can be fully recognised.